CONTROL AND PREVENTION OF DISTURBANCES OF THE NORMAL PHYSIOLOGY OF THE MUSCLE SYSTEM OF ATHLETES - Ilyin, A.B.; Cherkasov, A.D. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to study the factors that provoke muscle pathologies during the period of intense loads of basic training in preparation for the main starts of the season. Methods and structure of the study. A survey of 30 athletes under the age of 25 years was carried out using the methods of manual diagnostics, functional tests for lateroflexion (bends of the spine to the sides), as well as MRI examination of the state of the muscular corset of the spine. Results and conclusions. Uncompensated pathologies of the tissues of the spine occur due to the development of spastic conditions of the intervertebral muscles. Spastic conditions of the muscles of the spine are caused by a violation of the state of the human neuromuscular apparatus due to malnutrition - excessive consumption of foods containing starch and sugar, white rice, with active elimination of vitamin B1 against the background of high loads. Pain syndromes in the spine can be prevented and/or stopped by normalizing the nutrition structure.